Analysis and Design of Structures Made of Plastically Anisotropic Materials - Alexandrov, Sergei; Lang, Lihui (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Plastic anisotropy is a common property of many metallic materials. This property affects the analysis and design of structures and metal forming processes. The present edited collection of papers concerns analytic and numerical methods of structural and metal forming analysis and design using material models for anisotropic materials. Some qualitative features of rigid plastic solutions in anisotropic plasticity are investigated. Both rate-independent and rate-dependent constitutive equations are considered. The effect of plastic anisotropy on the distribution of residual stresses and strains is shown. Some papers deal with thermo-mechanical problems.